2021
DOI: 10.1007/s10567-020-00336-y
|View full text |Cite
|
Sign up to set email alerts
|

Foster Parents’ Parenting and the Social-Emotional Development and Adaptive Functioning of Children in Foster Care: A PRISMA-Guided Literature Review and Meta-Analysis

Abstract: Children in foster care (CFC) are at increased risk for negative developmental outcomes. Given the potential influence of foster parents’ parenting on the development of CFC, this literature review and meta-analysis provide an initial overview of how parenting factors in foster families relate to CFC’s developmental outcomes. We aimed to explore (1) whether foster parents’ parenting conceptualizations are related differently to various CFC developmental outcome variables and (2) how characteristics of foster p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 88 publications
4
5
0
1
Order By: Relevance
“…Vanderfaeillie et al [17] showed in their longitudinal study that problem behaviours in CFC were significantly associated with the use of negative parenting in foster mothers. Moreover, Chodura et al [18] found in their meta-analysis similar associations between parenting and child development in foster families, as had been previously found in biological families; however, most of the studies (34 out of 43) were cross-sectional. Additionally, Orme and Buehler [7] concluded that approximately 15 percent of foster parents manifest potentially poor or troubled parenting as reported by youth welfare workers (however, of note is that comparable studies in biological families are missing).…”
Section: Introductionsupporting
confidence: 62%
“…Vanderfaeillie et al [17] showed in their longitudinal study that problem behaviours in CFC were significantly associated with the use of negative parenting in foster mothers. Moreover, Chodura et al [18] found in their meta-analysis similar associations between parenting and child development in foster families, as had been previously found in biological families; however, most of the studies (34 out of 43) were cross-sectional. Additionally, Orme and Buehler [7] concluded that approximately 15 percent of foster parents manifest potentially poor or troubled parenting as reported by youth welfare workers (however, of note is that comparable studies in biological families are missing).…”
Section: Introductionsupporting
confidence: 62%
“…While parental practices are the specific behaviors and actions that parents enact when interacting with their children (e.g., helping them do their homework, asking them about their hobbies, etc. ), parenting style regards parents' overall attitude and behavior, which defines the emotional climate in which they raise their children [41][42][43]. Different parenting styles have been defined, with some regarded as less adaptive than others [41][42][43][44]: The authoritative parenting style is considered as the most adaptive and is characterized by clear boundaries and limits set for children by their parents, who nonetheless also display high sensitivity and emotional warmth; differently, the permissive parenting style, although also characterized by high sensitivity and warmth, foresees an indulgent parental behavior and overall lack of discipline, which renders it maladaptive.…”
Section: Introductionmentioning
confidence: 99%
“…), parenting style regards parents' overall attitude and behavior, which defines the emotional climate in which they raise their children [41][42][43]. Different parenting styles have been defined, with some regarded as less adaptive than others [41][42][43][44]: The authoritative parenting style is considered as the most adaptive and is characterized by clear boundaries and limits set for children by their parents, who nonetheless also display high sensitivity and emotional warmth; differently, the permissive parenting style, although also characterized by high sensitivity and warmth, foresees an indulgent parental behavior and overall lack of discipline, which renders it maladaptive. Further maladaptive parenting styles are the authoritarian and neglectful styles: The former is characterized by strict discipline and high demands but low levels of sensitivity and emotional support, whereas the latter is characteristic of parents who are neither emotionally involved nor set rules and demand discipline from children [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sollte sich z. B. auch bei längerer Beobachtungszeit ein ähnliches Ergebnis ergeben, hieße dies wohl für die Interventionsforschung, dass KiP keinen besonderen Zuschnitt von wirksamen Programmen zur Reduktion von Verhaltens-und Beziehungsproblemen brauchen, sondern auf dieselben Maßnahmen zurückgegriffen werden könnten, die sich aus der bisherigen entwicklungspsychopathologischen Forschung ableiten lassen (s. auch Chodura, Lohaus, Symanzik, Heinrichs & Konrad, 2021).…”
Section: Diskussion Diskussion Der Inhaltlichen Befundeunclassified